1989
DOI: 10.1111/j.1365-2125.1989.tb03505.x
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacokinetics and pharmacodynamics of perindopril in patients with hepatic cirrhosis.

Abstract: 1. Perindopril, a new ACE inhibitor, is a prodrug requiring conversion into its active form perindoprilat by hydrolysis in the liver. 2. The pharmacodynamics and pharmacokinetics of perindopril (8 mg oral) and perindoprilat (2 mg intravenously) were studied in a double‐blind randomised crossover study in a group of patients with compensated biopsy‐proven hepatic cirrhosis. 3. Blood pressure and heart rate responses were similar after the two routes of administration as were plasma renin activity and aldosteron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

1992
1992
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 15 publications
1
5
1
Order By: Relevance
“…On the other hand, an additional influence of portocaval shunting or the effects of concomitant therapy taken by half of the patients cannot be excluded. Finally, in contrast with our results, a previous study has shown that mild liver cirrhosis had no influence on perindopril disposition (Tsai et al, 1989). The reason for this discrepancy is unclear.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…On the other hand, an additional influence of portocaval shunting or the effects of concomitant therapy taken by half of the patients cannot be excluded. Finally, in contrast with our results, a previous study has shown that mild liver cirrhosis had no influence on perindopril disposition (Tsai et al, 1989). The reason for this discrepancy is unclear.…”
Section: Discussioncontrasting
confidence: 99%
“…A more severe hepatic dysfunction could explain the decrease in the deesterification of perindopril to perindoprilat observed in some of our patients. However, the finding that the maximum inhibition of plasma ACE activity in our group of cirrhotics (87%) was similar to that reported with perindopril in cirrhotic patients with mild hepatic impairment (89%, Tsai et al, 1989) as well as in patients with essential hypertension (80%, Lees & Reid, 1987c) suggests that, overall, no dosage adjustment of perindopril is required in patients with liver cirrhosis.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The evidence on the pharmacological response to RAASinhibitors in patients with cirrhosis is conflicting. Several studies demonstrated that the percentage of angiotensinconverting enzyme (ACE) inhibition in cirrhosis was not different than in healthy controls [60][61][62][63]. One found a largely decreased activation of enalapril to its active form in patients with cirrhosis, yet the effect on blood pressure was similar to the healthy controls suggesting that the patients are more sensitive to this effect [61].…”
Section: Altered Pharmacological Effectmentioning
confidence: 99%
“…However, the effect of aging (in the absence of hepatic, renal or cardiac dysfunction) on the pharmacokinetic profiles of these drugs is relatively small and usually of no clinical significance, [129][130][131] However, a significant decline in renal function, as a result of aging or disease, can cause clinically important alterations in the pharmacokinetics of active drugs and metabolites primarily eliminated by the kidney.l132-136] Drug and active metabolite accumulation occurs after chronic administration of ACE inhibitors in patients with renal impairment.l133-136] Hence, dosage adjustment may be necessary for most ACE inhibitors in patients with reduced renal function, Since fosinopril and its active metabolite are excreted by renal as well as biliary routes, dose reduction or adjustment of dosage schedule is not necessary for this drug unless there is concomitant hepatic dysfunction, [137,138] For benazepril and spirapril, dosage adjustment is not needed in patients with mild to moderate renal insufficiency (creatinine clearance >30 ml/min), [138] but dose reduction may be required in severe renal failure, However, the effect of aging (in the absence of hepatic, renal or cardiac dysfunction) on the pharmacokinetic profiles of these drugs is relatively small and usually of no clinical significance, [129][130][131] However, a significant decline in renal function, as a result of aging or disease, can cause clinically important alterations in the pharmacokinetics of active drugs and metabolites primarily eliminated by the kidney.l132-136] Drug and active metabolite accumulation occurs after chronic administration of ACE inhibitors in patients with renal impairment.l133-136] Hence, dosage adjustment may be necessary for most ACE inhibitors in patients with reduced renal function, Since fosinopril and its active metabolite are excreted by renal as well as biliary routes, dose reduction or adjustment of dosage schedule is not necessary for this drug unless there is concomitant hepatic dysfunction, [137,138] For benazepril and spirapril, dosage adjustment is not needed in patients with mild to moderate renal insufficiency (creatinine clearance >30 ml/min), [138] but dose reduction may be required in severe renal failure,…”
Section: Changes Affecting Pharmacokineticsmentioning
confidence: 99%